The water walkers - Williams, David; Aldrich-Blake, Pelham; Attenborough, David, 1926- (London : BBC Enterprises, 1981)
The surface of Britain's pond and stream is a miniature and unsuspected world where the laws of physics takes on anew meaning. Here water bends and surface tension become a terrible force. Specialist photography by London Scientific Films yields a startling unfamiliar view of this gossamer-thin habitat and its denizens - pond skaters and swamp spiders, whirligigs and water-boatmen. Why can some insects walk on the surface while others become hopelessly entrapped? Why dont whirligig beetles collide? What do pond skaters do in the rain? These are but a few of the questions answered in this fascinating and beautiful film
Keywords: Aquatic insects -- United Kingdom